Effect of Neem Oil Formulation on the Population of Soil Fungi and Disease Intencity of Cercospora Leaf Spot (Cercospora capsici) on Chilli Plants (Capsicum annuum) - Sri Hartati; Danar Dono; Rika Meliansyah; Mukhamad Agung Yusuf (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2018)
Soil fungi and cercospora leaf spot are soil inhabitants and plant disease, respectively, that usually occur on chilli grown area. Formulation of neem oil was reported to have a role as an environmentally friendly botanical pesticide. This research was objected to studying the effect of neem oil formulation on the population of soil fungi and its suppression on cercospora leaf spot intensity of chilli crop. The field experiment was arranged in the randomized complete block design. The treatments were the concentration of neem oil formulation, i.e. 0%, 1%, 1.25%, 1.50%, 1.75%, and 2.0%. In vitro experiment on the suppression of neem oil formulation on the predominant soil, fungi were arranged in the completely randomized design. The results showed that neem oil formulation did not affect the soil fungi population and cercospora leaf spot intensity. However,2.0% neem oil had the lowest soil population. Neem oil formulation at 1.75% caused the highest suppression on TMa01 isolate (49.81%), and 1.25%, 1.50%, 1.75% and 2.0% of neem oil formulation caused more than 50% suppression on TMf01 isolate in vitro. Neem oil formulation at 2.0% caused the highest suppression on cercospora leaf spot intensity (46.34%).Keywords: Azadirachta indica, botanical pesticide, neem oil